(3GdfLe GdRGgQ def jQjO WQjb GdMb GdXGgQs - (3eLghds; (3GdTYQGfj , YHO GdhgGH Hf CMeO Hf Ydj GdMfaj, CHh eMeO,J (B973 (3g` s
(3ChdgG (B:s
(3hHYO , agPG cJGH LeYJg ef GdWHbGJ GdcHQi dehdGfG GdTjN YHOGdhgGH GdTYQGfj QVi Gddg Yfg PcQJ ajg eG cGf efTWkG ddeQjOjf s
(3BNQgG (B:s
(3hUdi Gddg Ydi SjOfG eMeO EeGe GdeJbjf hMHjH GdYGdejf Je GdebUhO HMeO Gddg hYhfg hMSf Jhajbg s
(3JHUQI GdYfhGf (B:s
(3LeYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B218s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B444 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs